O pensamento crítico de Feuerbach: Razão, natureza e sensibilidade - Alencar, Mozart Oliveira (2020)
This study has the merit of investigating, not merely in a broad and generic sense, Ludwig Feuerbach’s motives for beginning his critique of religion, as well as indicating the thinker’s ethical and philosophical outputs, based on the details made possible in this work. As such, it must be noted that Feuerbach wrote during an era of considerable transformation in the field of thought, and, thus, this study focuses on his unique way of doing philosophy and on content from that period that has, until now, been little explored. Within that content, Feuerbach identifies in religion in general a unique dimension for understanding the human essence and its primordial relationship to nature and civilization. Yet religion leaves a “theophilosophical” legacy in the historical development of ideas, which causes human consciousness to develop sophisticated alternatives of alienating its own essence at the philosophical level. For this reason, the thinker complements his critique of religion with a critique of modernity and idealism as a key to understanding. Lastly, this study develops in a rather aphoristic manner the principles of a new philosophy, a proposal which will be developed in the future, and which no longer takes as its object the traditional split between man and God (in theology) or between reason and nature (in the case of modern philosophy), but rather a thought that visualizes the human being as an integral and immanent reality, incorporating the sensitivity of the human spirit by way of philosophical enlightenment. In short, this study examines the making of this new philosophy, rooted in the material and natural plane, into a “new religion,” or, in other words, the transference to atheistic philosophy and culture a role that had previously been attributed to religion.